Risk Factors for Acute Brucellosis in Patients on the Day of Admission at Selected Hospitals of Abbottabad, Pakistan - Hassan, Laiba; Ali, Shahzad; Syed, Muhammad Ali; Shah, Asim Ali; Abbasi, Shahid Ahmad; Tabassum, Sadia; Saeed, Usama; Melzer, Falk; Khan, Aman Ullah; El-Adawy, Hosny; Neubauer, Heinrich (Frontiers in Public Health, 2022)
Brucellosis is a neglected zoonotic disease of ruminants. It causes severe health problems in humans and significant economic loss. Only a limited number of studies have been conducted in Pakistan to determine the prevalence of human brucellosis and related risk factors. The objectives of the current cross-sectional study were to determine the prevalence of anti-Brucella antibodies in sera collected from symptomatic patients at three hospitals of Abbottabad using a commercial slide agglutination test (SAT) and to determine risk factors for brucellosis for these patients. Five hundred blood samples were collected. A questionnaire was filled in for each patient to obtain information on age, gender, living area, brucellosis associated symptoms, associated risk factors, pregnancy and abortion history. A total of 13.6% (n = 68) patients were found to be SAT positive and in 83.3% (n = 57) of these samples Brucella DNA was detected by genus specific RT-PCR for BCSP-31 gene. Statistical analysis was performed to determine odd ratios, risk ratios, 95% confidence intervals, and p-values. The prevalence of brucellosis by SAT was reported to be higher in women (14.6%, n = 44) than in men (12.1%, n = 24). The age group 25–50 years was found to be at higher risk for brucellosis (14.5%, n = 50) “animal contact” was reported as the main risk factor followed by “consumption of raw animal products.” Out of 131 pregnant women and 21 patients had abortion, the seropositivity of Brucellosis was 9.9% and 23.8%, respectively. The present study reports a striking prevalence of brucellosis among patients including pregnant women at three hospitals of Abbottabad. These findings may foster strategies for controlling human brucellosis at household level, raising of awareness about brucellosis in hospital and family doctors, and finally in setting up an eradication program in the dairy industry.